Healthy Lifetime (HL): An Internet-Based Behavioral Health Coaching Protocol for Older Adults - Flaherty-Robb, Marna; Calarco, Margaret; Butterworth, Susan; Struble, Laura; Harden, Karen; Franklin, Mary; Potempa, Stacia; Laughlin, Candia; Schmidt, Patricia; Policicchio, Judith; Yakusheva, Olga; Isaman, Deanna; et al. (Frontiers in Digital Health, 2022)
By 2060, the number of Americans 65 years and older will more than double, comprising nearly one-quarter of the population in the United States. While there are many advantages to living longer, a byproduct of aging is also a growing incidence of chronic illness and functional health limitations associated with a concurrent rise in chronic disease and disability that impair independent living in the community. We describe a personalized, behavioral health coaching protocol for early intervention that is delivered online to enhance a participant's independent functioning and to increase their self-care capacity with a goal to maintain independent living throughout aging. The electronic platform provides secure access to fillable surveys, health tracking, “just in time” communication with coaches and scheduling of two-way videos launched from the platform site. The 2-month protocol used two-way video conferencing which allowed high fidelity communication to sustain a complex behavioral intervention. Participants indicate high satisfaction with the intervention, the use of the platform, and the technology. While many health systems across the U.S. have ramped up virtual delivery of care in a proactive manner with now more than 70% of out-patient visits conducted through virtual delivery modes in some health systems, there remains much unevenness in this capability across the U.S. Our approach is to create a stable, interoperable, virtual outreach system for personalized professional health coaching that is complementary to medically oriented services that supports the health and functioning of participants as they age.